Local incentives and electric vehicle adoption - Askill Harkjerr Halse; Karen E. Hauge; Elisbeth T. Isaksen; Bjørn G. Johansen; Oddbjørn Raaum (University of Oslo, Department of Economics, 2022)
We study how the adoption of battery electric vehicles - a key technology for decarbonizing transportation - responds to two local privileges: road toll exemption and bus lane access. Combining rich Norwegian microdata with a quasiexperimental research design where we exploit household-level variations in incentives on work commutes, we find sizable and positive effects on electric vehicle ownership. The increase in electric vehicles from having road tolls and bus lanes on work commutes is offset by a similar decline in conventional vehicles. Road tolls also reduce brown driving, but lower CO2 emissions are largely explained by the existence of fewer conventional vehicles.
Keywords: H23; Q55; Q58; R41; R48; 330; electric vehicles; local incentives; road tolls; bus lanes